Developing Intercultural Language Learning (ILL) model to teach writing skills at Indonesian private universities - Haerazi Haerazi; Lalu Ari Irawan (EduLite: Journal of English Education, Literature and Culture, 2020)
This study was aimed at developing an intercultural language learning (ILL) model and finding out its effectiveness to increase students’ writing skills. The kind of this study was procedural research (R&D) design. This study was preceded with the development phases and continued by field-testing. The field-testing was conducted by using a quasi-experimental method to know the effectiveness of the developed learning model. The sample included 64 students. The students were divided into two groups and each group consisted of 32 students. One group was the experimental group taught by suing the ILL model and the other group was the control group taught by implementing the conventional learning model. The mean score of students taught by ILL model was 80.34 and those taught by conventional one was 69.97. The data were defined as normal and homogeneous data because the value of sig. was higher than sig. level 0.05. Based on the ANOVA test, the value of sig. (0,000) was lower than the sig. level 0.05. It means there is a significantly different achievement of students taught using an ILL model rather than the conventional learning model. The result informed ILL model was more effective than the conventional one in the teaching of writing skills.